Exploring Tourists Interpretations of Destination Innovativeness, Warmth, and Competence in Encouraging Revisit Intention in Aceh Province: A Phenomenological Approach - Kesuma, Teuku Meldi; Siregar, M. Ridha; Halim, Hendra; Umuri, Khairil; Zikran, Ghrina; Humaira, Radhia; Raihana, Rana (Universitas Syiah Kuala, 2025)
This study explores how domestic tourists interpret destination innovativeness, warmth, and competence as key factors influencing their intention to revisit tourist destinations in Aceh Province, Indonesia. Using a qualitative phenomenological approach, the research focuses on tourists lived experiences and subjective meanings derived from their interactions with innovative and culturally rich destinations. Data were collected through in-depth interviews and participatory observations at four major destinations: Banda Aceh, Sabang, Takengon, and Lhokseumawe. The findings reveal that destination innovativeness is perceived not only through technological and infrastructural improvements but also through efforts to preserve cultural authenticity and enhance comfort. Warmth is associated with the friendliness and sincerity of local communities, while competence reflects professional management, reliable information, and environmental care. Collectively, these elements form emotional and cognitive meanings that foster tourists intention to revisit. Theoretically, this study extends the Tourist Perceived Destination Innovativeness and Stereotype Content Model frameworks, while practically highlighting the importance of experience-based, socially warm, and competence-driven destination management in sustaining tourist loyalty.